2008
DOI: 10.1002/hep.22278
|View full text |Cite
|
Sign up to set email alerts
|

Lack of inducible nitric oxide synthase leads to increased hepatic apoptosis and decreased fibrosis in mice after chronic carbon tetrachloride administration

Abstract: The role of nitric oxide (NO) in liver injury and fibrosis is unclear. The purpose of this study was to determine whether inducible NO synthase deficiency (iNOS ؊/؊ ) affects liver injury and fibrosis produced in mice by chronic carbon tetrachloride (CCl 4 ) administration. Wildtype (WT) or iNOS ؊/؊ mice were subjected to biweekly CCl 4 injections over 8 weeks, whereas controls were given isovolumetric injections of olive oil. Serum aminotransferases were lower after CCl 4 in the iNOS ؊/؊ than in the WT mice, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 20 publications
4
53
0
1
Order By: Relevance
“…Additionally, since tissue inhibitor of metalloproteinase is reportedly also synthesized in the liver along with MMPs after CCl 4 treatment, there may be a fine balance between MMPs and tissue inhibitor of metalloproteinase. 34,35 Our data have also shown that the majority of PEDFinduced PPAR␥ in HSCs remains in the cytoplasm, rather than the nucleus. Similar subcellular retention of PPAR␥ has been reported by others in macrophage-like RAW 264 cells, differentiating 3T3-L1 preadipocytes, and normal human urothelial cells, and this cytoplasmic retention is related to the nitration, lipid droplet interaction, and tyrosine phosphorylation of PPAR␥.…”
Section: Discussionsupporting
confidence: 56%
“…Additionally, since tissue inhibitor of metalloproteinase is reportedly also synthesized in the liver along with MMPs after CCl 4 treatment, there may be a fine balance between MMPs and tissue inhibitor of metalloproteinase. 34,35 Our data have also shown that the majority of PEDFinduced PPAR␥ in HSCs remains in the cytoplasm, rather than the nucleus. Similar subcellular retention of PPAR␥ has been reported by others in macrophage-like RAW 264 cells, differentiating 3T3-L1 preadipocytes, and normal human urothelial cells, and this cytoplasmic retention is related to the nitration, lipid droplet interaction, and tyrosine phosphorylation of PPAR␥.…”
Section: Discussionsupporting
confidence: 56%
“…Moreover, NO is hypothesized to be a potential regulatory effector for prolidase and may regulate matrix metalloproteinase activity. An iNOS knockout study revealed decreased collagen accumulation in chemically-induced liver fibrosis, (24). ADMA promotes the dissociation of the ferrous-dioxy species from the heme group of NOS, resulting in the production of superoxide rather than NO.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Moreover, the NO generated by the activity of the inducible form of NO synthase, which is highly responsive to pro-inflammatory cytokines and endotoxemia, has been proposed to induce liver damage and facilitate the deposition of collagen. 24 TNF-a and MCP-1 have an important role in the development of fibrosis as pro-inflammatory molecules contributing to the activation of HSC and to the recruitment of myofibroblasts, macrophages and other effector cells to sites of tissue injury. 16,17 As we have recently showed in a model of acute liver injury produced by ischemia-reperfusion complicated by endotoxemia, 13 Rimonabant appears to exert its protective activity also by promoting the synthesis of IL-10 and SOCS-3.…”
Section: Endocannabinoids and Liver Cirrhosismentioning
confidence: 99%